Raising the level for #1#1#1=≤ ==≥ =PrFrReGL_n. (10th June 2014) - THORNE, JACK A.
Abstract: We prove a simple level-raising result for regular algebraic, conjugate self-dual automorphic forms on GL_n . This gives a systematic way to construct irreducible Galois representations whose residual representation is reducible.